2001
DOI: 10.1002/jbm.1247
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylapatite with substituted magnesium, zinc, cadmium, and yttrium. II. Mechanisms of osteoblast adhesion

Abstract: The present in vitro study investigated osteoblast adhesion on hydroxylapatite (HA) doped with either cadmium (Cd), zinc (Zn), magnesium (Mg), or yttrium (Y). Compared with any other dopant tested in the present study, osteoblast adhesion was significantly (p < 0.05) greater on HA doped with Y after 4 h; in addition, osteoblast adhesion increased with concentration (2-7 mol%) of Y in HA. The findings that HA doped with greater amounts of Y adsorbed higher concentrations of calcium and, subsequently, of vitrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(166 citation statements)
references
References 13 publications
4
160
1
1
Order By: Relevance
“…30 Igarashi and Yamaguchi further demonstrated that orally administered zinc resulted in an increase in the mineral density of remodeled rat femoral bone. 31 Zinc-doped calcium phosphate ceramics have been shown to promote osteoblast proliferation, 32 encourage attachment, 33 and enhance alkaline phosphatase (ALP) expression 34 in vitro. Oki et al established that osteoblastic cells cultured on a zinc-containing silica based sol-gel glass (64 mol % SiO 2 -26 CaO-5 ZnO -5 P 2 O 5 ) underwent increased ALP expression relative to cells cultured on tissue culture polystyrene.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Igarashi and Yamaguchi further demonstrated that orally administered zinc resulted in an increase in the mineral density of remodeled rat femoral bone. 31 Zinc-doped calcium phosphate ceramics have been shown to promote osteoblast proliferation, 32 encourage attachment, 33 and enhance alkaline phosphatase (ALP) expression 34 in vitro. Oki et al established that osteoblastic cells cultured on a zinc-containing silica based sol-gel glass (64 mol % SiO 2 -26 CaO-5 ZnO -5 P 2 O 5 ) underwent increased ALP expression relative to cells cultured on tissue culture polystyrene.…”
Section: -24mentioning
confidence: 99%
“…Although the zinc content in human bone ranges between 124 and 312 lg/g, 61 other work such as that of Webster et al 33 showed that osteoblast attachment can be increased on the surface of 2% Zn-hydroxyapatite ceramics over that of hydroxyapatite, despite having concentrations of zinc several time that of natural bone. The HCA forming sol gels in this study contained 1.3-2% Zn within the apatite layer at 4 h. The dual ability of the sol-gel derived SiO 2 /CaO/ZnO system to release low levels of zinc and form a Zn-containing bioactive calcium phosphate layer may allow for improved hard tissue regeneration in orthopedic, craniomaxillofacial, or dental applications.…”
mentioning
confidence: 97%
“…These endothelial cells are important in new blood vessels formation, which in turn is important for providing essential nutrients to newly forming bone cells. Additionally, magnesium has been shown to improve the osteogenic differentiation of cells, and indirectly, bone formation [16,17]. Moreover, our previous results showed that 50 wt% MCP gelatin sponges have improved mesenchymal cellular proliferation and alkaline phosphatase activity in comparison with the 0 wt% gelatin sponges and improved osteocalcin activity in comparison with the 90 wt% MCP gelatin sponges.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are supported by Nikolovski et al who showed that untreated (conventional) PGA and PLGA (75:25) adsorbed vitronectin when exposed to serum-containing media (Nikolovski and Mooney 2000), and provides further evidence of the enhanced potential of nano-dimensional PLGA to adsorb such critical proteins. While direct evidence has been provided to link the effect of vitronectin conformation, etc., on nanophase ceramics to increased osteoblast cell density (Webster et al 2002), the exact mechanism behind the differing responses of vascular smooth muscle cells, endothelial cells, and fibroblasts to nanostructured PLGA remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%